2022
DOI: 10.1080/15440478.2022.2126424
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hygrothermal Aging on Mechanical Properties and Damage Mechanisms of Hemp-Reinforced Biocomposites

Abstract: Biocomposites are being developed for structural applications, particularly in the automotive industry. The use of plant fibers as reinforcement is a first step towards the development of ecomaterials but it is necessary to use also a more eco-friendly matrix. In this paper, woven hemp composites impregnated with two different eco-polymers are compared: hemp/Greenpoxy and hemp/Elium. Greenpoxy is a partially bio-based thermoset resin and Elium is a recyclable thermoplastic polymer. The influence of various hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Natural fibers have a hydrophilic behavior, which can have consequences on the fiber/matrix interfacial adhesion [21]. Several studies have shown that the water uptake in natural fiber-reinforced composites has an adverse effect on rigidity and strength [22][23][24][25][26] and some of them have focused Micro 2023, 3 on the influence of the water temperature on the absorption properties [27,28]. Malloum et al studied the influence of water immersion time on two cross-ply laminates ([0/90] s and [+45/−45] s ) of flax/Greenpoxy composite.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers have a hydrophilic behavior, which can have consequences on the fiber/matrix interfacial adhesion [21]. Several studies have shown that the water uptake in natural fiber-reinforced composites has an adverse effect on rigidity and strength [22][23][24][25][26] and some of them have focused Micro 2023, 3 on the influence of the water temperature on the absorption properties [27,28]. Malloum et al studied the influence of water immersion time on two cross-ply laminates ([0/90] s and [+45/−45] s ) of flax/Greenpoxy composite.…”
Section: Introductionmentioning
confidence: 99%